2020
DOI: 10.3390/nano11010002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Delivery of Nanocurcumin in Central Nervous System Related Disorders

Abstract: Nutraceuticals represent complementary or alternative beneficial products to the expensive and high-tech therapeutic tools in modern medicine. Nowadays, their medical or health benefits in preventing or treating different types of diseases is widely accepted, due to fewer side effects than synthetic drugs, improved bioavailability and long half-life. Among herbal and natural compounds, curcumin is a very attractive herbal supplement considering its multipurpose properties. The potential effects of curcumin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 233 publications
0
19
0
1
Order By: Relevance
“…Even though various methods for crossing the BBB have been developed, significant issues still make brain drug delivery problematic. The use of customized nanocarriers to preserve drugs while allowing them to pass across the BBB appears to be a successful approach [ 68 ].…”
Section: Therapeutic Applications Of Nanocurcumin Over Curcuminmentioning
confidence: 99%
“…Even though various methods for crossing the BBB have been developed, significant issues still make brain drug delivery problematic. The use of customized nanocarriers to preserve drugs while allowing them to pass across the BBB appears to be a successful approach [ 68 ].…”
Section: Therapeutic Applications Of Nanocurcumin Over Curcuminmentioning
confidence: 99%
“…Moreover, it was also found that the expression of Apolipoprotein J or clusterin was decreased, thereby reducing the severity of the disease. Various types of curcumin nanocarriers, which include dendrimers, nanoparticle conjugates, micelles, and bio-based nanomaterials and their associated properties such as solubility, stability, etc., were studied in [ 59 ]. It was investigated that the nanocurcumin drug delivery system could actually lead to improved efficiency in the diseases related to CNS.…”
Section: Uses Of Nanocurcuminmentioning
confidence: 99%
“…These products increase the functionality or bioavailability of nutrients, showing beneficial effects on human health by preventing the onset of several pathologies, including cancer and several cardiovascular and neurodegenerative disorders. However, 70% of compounds with possible usage as nutraceuticals have poor aqueous solubility leading to difficulty crossing cell membranes [ 7 ]. This problem is addressed by using different formulation approaches such as particle size reduction (nano-sizing) and the use of the amorphous form and lipid-based drug delivery systems, albeit with specific drawbacks that must always be taken into consideration.…”
mentioning
confidence: 99%
“…The authors discuss the most recent approaches of nanotechnology to overcome the poor bioavailability of nutraceuticals, highlighting the pros and cons of several nanodelivery systems. Nutraceuticals include dietary supplements and functional foods [ 4 ] that give benefit to human health by positively affecting the immune system and strengthening it in these turbulent days of the COVID-19 pandemic [ 7 ]. The body’s immune responses to nanonutraceuticals are discussed in relation to vitamins (C, D, E, B12, folic acid), minerals (Zn, Fe, Se), antioxidants (carotenoids, coenzyme Q10, polyphenols, curcumin, omega-3 fatty acids), and probiotics [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation